Determinants of exports in the G7-countries - Susanne Lapp; Joachim Scheide; Ralph Solveen (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
Real effective exchange rates and economic activity in trading partner countries have a considerable impact on real exports of the G7-countries. Using an errorcorrection framework we find that the short-run and the long-run effects differ substantially between the countries. The relative importance of both influences is demonstrated in a simulation with standardized shocks. For five countries, the effects are more or less the same; in Japan, however, the exchange rate effect dominates the effect stemming from foreign economic activity, the opposite is true for France. Finally, exchange rate volatility does not systematically affect export growth in the majority of the countries.
Keywords: C22; F17; 330; Außenhandelselastizität; Kaufkraftparität; Schätzung; G-7-Staaten